2019
DOI: 10.7759/cureus.4630
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer, Gender Identity, and Testosterone Replacement Therapy in Klinefelter Syndrome: A Case Report and Literature Review

Abstract: Klinefelter syndrome (KS), karyotype 47, XXY, is a common cause of hypogonadism in males. Patients with this condition often experience symptoms of gonadal failure, which can precipitate gender identity challenges. Treatment with testosterone replacement therapy (TRT) can combat these symptoms by improving sexual function, muscle mass, bone health, and virilization, thereby enhancing the quality of life (QOL). Although TRT is often employed in patients with KS, there is a concern that the application of exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Pathognomonic small testicular volume was reported in two individuals 37,44 . Two individuals had venous thromboembolic events before the initiation of estradiol 40,41 . Of the two case reports that reported on semen analysis, both had azoospermia 37,38 .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Pathognomonic small testicular volume was reported in two individuals 37,44 . Two individuals had venous thromboembolic events before the initiation of estradiol 40,41 . Of the two case reports that reported on semen analysis, both had azoospermia 37,38 .…”
Section: Resultsmentioning
confidence: 96%
“…Of the seven case studies that reported serum testosterone concentration, five (71%) had serum testosterone concentrations below the lower limit of the male reference range. In all, seven articles reported on the prescription of testosterone therapy in nine individuals, 31,37,38,40,41,44,45 three of whom had poor compliance or ceased testosterone following the development of secondary male sex characteristics 41,44,45 . One individual ceased testosterone therapy after days, 38 while another ceased while receiving treatment for prostate cancer 40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, among men with congenital MH, the occurrence of PCa during T treatment is so vanishingly rare that we have been able to identify less than 10 published reports [49].…”
Section: Testosterone Treatment and Androgen-sensitive Cancersmentioning
confidence: 90%